Pengembangan Modul Katekese Perkawinan Berbasis Keluarga Sebagai Fondasi Pendampingan Pasangan Muda Pasca-Pernikahan - Sember Sawo, Emilianus (Sepakat : Jurnal Pastoral Kateketik, 2024)
This research aims to develop a family-based marriage catechesis module as a foundation for post-wedding accompaniment of young Catholic couples. Using a qualitative approach with document study, the research identifies five key gaps in Catholic couple accompaniment: discontinuity of pastoral care, non-transformative pedagogical approaches, minimal involvement of experienced families, lack of content contextualization, and weak communal support. In response, a module with spiral structure was developed for continuous accompaniment during the first four years of marriage, integrating theological-spiritual, relational-psychological, social-communal, and practical-contextual dimensions. This module operationalizes the concept of "family as pastoral subject" through a mentoring model where experienced couples accompany newly married couples. Implementation requires systematic selection and formation of mentor couples, balanced accompaniment structures, and adaptive approaches. Integration strategies within parish systems include institutional support, appropriate ecclesiological approaches, a "hub and spoke" model, gradual implementation, and utilization of digital technology. This research offers a more participatory, relational, and contextual approach to marriage pastoral care.